The pastor theologian : resurrecting an ancient vision - Hiestand, Gerald, 1974- (Grand Rapids, Michigan : Zondervan, 2015)
Pastoral ministry today is often ruled by an emphasis on short-sighted goals, pragmatic results, and shallow thinking. Unfortunately, those in the academy tend to have the opposite problem, failing to connect theological study to the pressing issues facing the church today. Contemporary evangelicalism has lost sight of the inherent connection between pastoral leadership and theology. This results in theologically anemic churches, and ecclesially anemic theologies. Todd Wilson and Gerald Hiestand contend that among a younger generation of evangelical pastors and theologians, there is a growing appreciation for the native connection between theology and pastoral ministry. At the heart of this recovery of a theological vision for ministry is the re-emergence of the role of the "pastor theologian." The Pastor Theologian presents a taxonomy of the pastor-theologian and shows how individual pastors -- given their unique calling and gift-set -- can best embody this age-old vocation in the 21st century. They present three models that combine theological study and practical ministry to the church: the local theologian -- a pastor theologian who ably services the theological needs of a local congregation; the popular theologian -- a pastor theologian who writes theology to a wider lay audience; the ecclesial theologian -- a pastor theologian who writes theology to other theologians and scholars. Raising the banner for the pastor as theologian, this book invites the emerging generation of theologians and pastors to reimagine the pastoral vocation along theological lines, and to identify with one of the above models of the pastor theologian.
Pastor or theologian?: a division of labor, a crisis of identity -- The pastor theologian in historical perspective: from the Apostolic Fathers to the Enlightenment -- The great divorce: the demise of the pastor theologian in Europe and North America -- The theological anemia of the church -- The ecclesial anemia of theology -- The pastor theologian: a taxonomy -- The pastor theologian as ecclesial theologian -- On being an ecclesial theologian in a local church -- The future of a movement, the renewal of the church.
Includes bibliographical references and index.
Keywords: Pastoral theology